1986
DOI: 10.1111/j.1365-2818.1986.tb02706.x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic observation and video recording of cellular response to sudden changes in environment

Abstract: SUMMARY A method to record responses of single cells to rapid changes in their environment is described. A rectangular glass microcapillary is filled with the cell suspension under investigation and placed under a light microscope. With the aid of a micromanipulator a smaller microcapillary with a narrowed tip, which was still over 10 times wider than the cell diameter, is driven into the larger, cell containing, microcapillary. The environment of the cells is changed by injecting a new medium via the smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Further, Kochen (1962) saw 'propulsive movements' of cells. Video recordings of haemolysing red blood cells were made by Eskelinen & Coakley (1986) without discussion of the cellular movements on record (compare b with c in their fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Kochen (1962) saw 'propulsive movements' of cells. Video recordings of haemolysing red blood cells were made by Eskelinen & Coakley (1986) without discussion of the cellular movements on record (compare b with c in their fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…In their hands, observations could be made as little as 0.1–0.3 s after the change of medium. Eskelinen & Coakley (1986) developed an apparently useful method for changing the medium around cells under the microscope. They used it successfully for prelytic and lytic studies of red cells.…”
Section: Introductionmentioning
confidence: 99%
“…x 40 objective, a video-recording system, and a drug injection system described earlier (Eskelinen and Coakley 1986;Eskelinen 1987). The experiments involved bringing the cells in an isotonic phosphatebuffered NaCl solution in a rectangular microcapillary into focus under a light microscope, at which point video recording commenced.…”
Section: Methodsmentioning
confidence: 99%
“…By video recording the shape transformations of erythrocytes under a light microscope, it is possible to measure the kinetics of the influence of membrane-active dmgs on the cell membrane (Eskelinen and Coakley 1986). In the previous paper of the present series (Eskelinen 19871, it has been shown that the kinetics of these shape transformations depend on the ambient drug concentration.…”
Section: Introductionmentioning
confidence: 99%